2000
DOI: 10.1002/1521-396x(200009)181:1<59::aid-pssa59>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Optical Study of Some Interstitial-Related Centres in CVD Diamond

Abstract: Luminescence and optical transmittance measurements were performed on irradiated natural diamond crystals and on synthetic films. Their results show that variations in luminescence with annealing can be due to changes in the non-radiative processes rather than in the concentration of the investigated centre. In particular, emission from the interstitial-related 3H centre increases when the neutral vacancy (GR1) anneals out, showing that the GR1 can effectively quench 3H emission. The 3H centre was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…9a). This is consistent with the results of Iakoubovskii and Adriaenssens (2000) and Iakoubovskii et al (2001) who found that most of the 3H absorption disappears upon annealing at well below 400 °C.…”
Section: Changes Upon Thermal Annealingsupporting
confidence: 93%
“…9a). This is consistent with the results of Iakoubovskii and Adriaenssens (2000) and Iakoubovskii et al (2001) who found that most of the 3H absorption disappears upon annealing at well below 400 °C.…”
Section: Changes Upon Thermal Annealingsupporting
confidence: 93%
“…In this letter, we report the selective creation of single color centers in diamond emitting at = 470.5 nm, which is known as TR12 line. [16][17][18] It was proposed that this center contains an interstitial carbon atom in a hexagonal site. 19 Although TR12 line has been observed in the luminescent spectrum of diamond decades ago, it was not clear whether luminescence quantum yield is high enough to detect single centers.…”
mentioning
confidence: 99%
“…21 In contrast to NV, the TR12 centers are less stable, annealing at temperatures above 800°C destroys major part of the 470 nm absorption. 16,22 Figure 1 shows a confocal microscopy fluorescence image where the implanted pattern can be clearly seen. The ion dose was 2000 ions per spot and each spot in the figure consists of several color centers.…”
mentioning
confidence: 99%
See 2 more Smart Citations